2021
DOI: 10.7759/cureus.15389
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Double-Positive Optic Neuritis: A Case of Aquaporin-4 and Myelin Oligodendrocyte Glycoprotein Antibody Seropositivity

Abstract: Optic neuritis (ON) causes acute vision loss with typical and atypical profiles, serological markers, imaging findings, and clinical outcomes depending on the associated underlying pathophysiology. Neuromyelitis optica (NMO) and myelin oligodendrocyte glycoprotein antibody disease (MOGAD) are the usual causes of acute severe sequential or simultaneous bilateral optic neuritis. These conditions are usually accompanied by multi-level spinal cord demyelination, and notably, they are typically positive for either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Fifty-three relevant studies were identified after title and abstract screening. After reading the full texts and reviewing the references of the retrieved articles, 35 studies were finally included in the qualitative synthesis, of which 14 were retrospective studies [ 11 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and 21 were case reports [ 12 , 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. A total of 113 patients (46 males and 67 females) were reported to show the coexistence of MOG-IgG and neuronal or glial antibodies in these 35 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three relevant studies were identified after title and abstract screening. After reading the full texts and reviewing the references of the retrieved articles, 35 studies were finally included in the qualitative synthesis, of which 14 were retrospective studies [ 11 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and 21 were case reports [ 12 , 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. A total of 113 patients (46 males and 67 females) were reported to show the coexistence of MOG-IgG and neuronal or glial antibodies in these 35 studies.…”
Section: Resultsmentioning
confidence: 99%
“… 68 , 75 Given the overall rarity of double positive cases based on the results of the larger studies, and considering the superior specificity of the AQP4-IgG test compared to the MOG-IgG test, and that a reliable cell-based-assay (CBA) for detecting MOG-IgG has been available just recently (2017), there is a high possibility that most of the double positive cases may likely be AQP4-IgG + NMOSD with false positive MOG-IgG test results, especially in reports made before this time with using enzyme-linked immunosorbent assay (ELISA). 68 , 75 …”
Section: Discussionmentioning
confidence: 99%
“…There have been a few reported literature showing double-seropositive (MOG-positive and AQP4-positive) optic neuritis and myelitis. 2,3 Double-positive NMOSD is found to have a high relapse rate and residual disability with MRI of the brain showing MS-like brain lesions in two-thirds of patients, while MRI of the spine showing edematous spinal cord from cervical to conus region. 2 APS at onset can delay the diagnosis of NMOSD causing further neurologic deficits in the form of optic neuritis, transverse myelitis, or brainstem syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Double seropositivity in NMOSD has been rarely reported in literature. 2,3 We report a rare case of APS as an initial presentation of double-seropositive AQP4 and MOG antibodies.…”
mentioning
confidence: 96%